Faktor-faktor yang Mempengaruhi Efektiftas Iklan pada Jejaring Sosial Media PT. Beth Rapha Agave Insani - Kezia Raharjo Gunawan; Saparso Saparso (Ilmiah Manajemen Bisnis, 2019)
Abstract — Competition in the digital industry makes entrepreneurs develop strategies so that their products or services can be known to the public. Beth Rapha Agave Insani is engaged in the feld of health and promotion through social media which is believed to be able to reach a broader market segment at a cost that is not too expensive. Beth Rapha Agave Insani, who has carried out promotions through e-mail and the web, said promotional advertisements experienced the same results year after year. The problem faced by Beth Rapha Agave Insani is how to design ads that are unusual, creative and can attract the attention of the audience so that the ads can be effective and have an impact on Beth Rapha. This study will analyze the effect of ad appeal, ad content and frequency of ad serving on the effectiveness of advertisements on Beth Rapha’s social media. This research uses the SMART PLS 3 program. The population used is the people who come to the clinic and who follow or follow Beth Rapha’s social media accounts. The sample used as many as 100 people with a purposive sampling method. The results showed that the attractiveness of advertisements, ad content and frequency of views had a positive and signifcant effect on the effectiveness of advertisements through consumer response. Thus, Beth Rapha must pay attention to these three things to produce effective advertising by looking at consumer responses so they get the right results. Keywords — ad appeal, ad content, frequency of views, consumer response, ad effectiveness